2020
DOI: 10.1166/jmihi.2020.3066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a 12-Week Intradialytic Exercise on Patients’ Blood Indices, Physical Performance, and Quality of Life

Abstract: This study aims to examine the effect of a 12-week intradialytic exercise program on patients’ blood indices, physical performance, and quality of life. Forty-six outpatients who were diagnosed with end-stage renal failure by a nephrologist and received hemodialysis therapy for six months or longer were recruited. The data were analyzed using SPSS and Kruskal-Wallis test was employed to analyze the continuous variables. Among blood indices, Hematocrit decreased significantly after aerobic and complex exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…At the same time of transmission, the original gene can obtain a new pathogenic gene; or it was previously encoded in a mobile plasma but inserted into the chromosome after mutation [ 29 ]. Urinary bacterial infection is a common infectious disease, mainly including asymptomatic bacteriuria, cystitis, and pyelonephritis.…”
Section: Theoretical Basismentioning
confidence: 99%
“…At the same time of transmission, the original gene can obtain a new pathogenic gene; or it was previously encoded in a mobile plasma but inserted into the chromosome after mutation [ 29 ]. Urinary bacterial infection is a common infectious disease, mainly including asymptomatic bacteriuria, cystitis, and pyelonephritis.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Nine studies 35,36,38,39,41,52,54,55,57 reported the detailed method of randomization, and the others 37,40,[42][43][44][45][46][47][48][49][50][51]53,56 reported randomization but did not describe a specific method. Five studies 35,36,39,48,54 completed allocation concealment.…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%
“…Six studies 40,[45][46][47]54,55 with 169 participants reported STS30, and all interventions of these studies were conducted during dialysis. ICARE significantly improved the STS30 compared with UC in MHD patients…”
Section: Sts30mentioning
confidence: 99%
See 2 more Smart Citations